Purification, characterization and cellular localization of 5'-nucleotidase from Torpedo electric organ. - Grondal, E J (1987)
5'-Nucleotidase was isolated from the electric organ of the electric ray Torpedo marmorata after solubilization in Triton X-100 and deoxycholate by affinity chromatography on concanavalin A-Sepharose and AMP-Sepharose. The purified enzyme has a Km for AMP of 38 microM, with a maximal velocity of 31 units/mg of protein. Of the purine and pyrimidine mononucleotides, AMP is hydrolysed most effectively. beta-Glycerophosphate, phosphoenolpyruvate and p-nitrophenyl phosphate are not substrates for the enzyme. Adenosine 5'-[alpha, beta-methylene]diphosphate, ADP and ATP are competitive inhibitors in this order of potency. Concanavalin A inhibits enzyme activity in a non-competitive manner. Whereas Mg2+, Ca2+ and Sr2+ activate enzyme activity in the millimolar range, Hg2+, and in particular Pb2+ and Zn2+, inhibit enzyme activity. On SDS/polyacrylamide-gel electrophoresis the enzyme has an apparent Mr of 62000, whereas that of the native deoxycholate-enzyme complex is 131000. An antiserum raised against the native enzyme inhibits enzyme activity. Inhibition studies suggest the presence of tissue-specific variants of the enzyme. By immunohistochemical analysis the enzyme can be localized to the ramifications of nerve terminals in the electric organ.